Predictors of health-related quality of life changes after lifestyle intervention in persons at risk of type 2 diabetes mellitus - Nilsen, Vegard (Springer International Publishing, 2014)
PURPOSE: To assess health-related quality of life (HRQOL) of subjects at risk of type 2 diabetes undergoing lifestyle intervention, and predictors for improved HRQOL. METHODS: The Finnish Diabetes Risk Score was used by general practitioners to identify individuals at risk. Low-intensity interventions with an 18-month follow-up were employed. HRQOL was assessed using the SF-36 at baseline and compared with results from a general Norwegian population survey and further at 6 and 18 months. Simple and multiple linear regression analyses were applied to identify predictors of changes in HRQOL of clinical importance. RESULTS: Two hundred and thirteen participants (50 % women; mean age: 46 years, mean body mass index: 37) were included: 182 returned for 18-month follow-up, of whom 172 completed the HRQOL questionnaire. HRQOL was reduced with clinical significance compared with general Norwegians. The mean changes in HRQOL from the baseline to the follow-up were not of clinical importance. However, one out of three individuals achieved a moderate or large clinical improvement in HRQOL. The best determinant for improved HRQOL was obtained for a composite, clinically significant lifestyle change, i.e. both a weight reduction of at least 5 % and an improvement in exercise capacity of at least 10 %, which was associated with an improvement in five out of the eight SF-36 domains. CONCLUSION: Subjects at risk of type 2 diabetes report a clinically important reduction in HRQOL compared with general Norwegians. The best predictor of improved HRQOL was a small weight loss combined with a small improvement in aerobic capacity.